Pacing Characteristics of His Bundle Pacing vs. Left Bundle Branch Pacing: A Systematic Review and Meta-Analysis - Zhuo, Wen; Zhong, Xiaojie; Liu, Hualong; Yu, Jianhua; Chen, Qi; Hu, Jinzhu; Xiong, Qinmei; Hong, Kui (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: His bundle pacing (HBP) is a physiological pacing strategy which aims to capture the His bundle-Purkinje system and activate the ventricles in a synchronous fashion. Left bundle branch pacing (LBBP) is a newly discovered physiologic pacing technique similar to HBP. We conducted this meta-analysis to compare the pacing parameters and clinical results between HBP and LBBP. Methods: We systematically retrieved studies using the PubMed, Embase database and Cochrane Library. Mean difference (MD) and relative risk (RR) with their 95% confidence intervals [CIs] were used to measure the outcomes. A random-effect model was used when studies were of high heterogeneity. Results: Seven studies containing 867 individuals were included. Compared to HBP, LBBP was associated with higher implant success rates (RR: 1.12, 95%CI: 1.05 to 1.18; I2 = 60%, P=0.0003), lower capture threshold at implantation (V/0.5ms) (MD: 0.63, 95% CI: 0.35 to 0.90, I2 = 89%, P<0.0001) and capture threshold at follow-up (V/0.5ms) (MD: 0.76, 95% CI: 0.34 to 1.18, I2 = 93%, P=0.0004), larger sensed R wave amplitude (mV) at implantation (MD: 7.23, 95% CI: 5.29 to 9.16, P<0.0001) and sensed R wave amplitude (mV) at follow-up (MD: 7.53, 95% CI: 6.85 to 8.22, P<0.0001). In LBBP recipients, greater QRS reduction was found in the paced QRS duration at follow-up compared to HBP recipients at follow-up (MD: 6.12, 95% CI: 1.23 to 11.01, I2 = 0%, P=0.01). No statistical differences were found in procedure duration, fluoroscopy time, native LVEF, LVEF improvement, native QRS duration, as well as QRS reduction from the native QRS duration versus paced QRS duration at implantation. Conclusion: Current evidence suggests that pacing characteristics are better in LBBP compared to HBP. Further prospective studies are needed to validate the clinical advantages of LBBP. Key Words: His bundle pacing; Left bundle branch pacing; Prognosis; Physiologic pacing; Pacing parameters